A super black composite coating based on carbon nanomaterials and preparation method thereof
By using composite coating of carbon nanomaterials in ultra-black materials, combined with ink direct writing 3D printing and spraying technology, in-situ ice crystal induced self-assembly technology to build a vertical and orderly micro-nano honeycomb structure, the absorption of existing ultra-black materials is solved The problems of insufficient rate and poor mechanical properties have achieved high-efficiency light absorption and mechanical properties, and are suitable for optical systems and new energy fields.
Patent Information
- Application Number
- CN202411312285.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-20
AI Technical Summary
Existing ultra-black materials have problems such as insufficient absorption rate, poor mechanical properties, poor UV radiation resistance and difficulty in taking into account both mechanical properties and light absorption properties in the fields of optical systems and solar energy utilization, especially in large-area preparation and controllable microstructures. There are challenges in the aspects.
Using composite coating of carbon nanomaterials, by mixing carbon nanoparticles, multi-walled carbon nanotubes and graphene with binder, combined with ink direct writing 3D printing technology and spraying technology, combined with in situ ice crystal induced self-assembly Technology, to construct a vertically arranged micro-nano cell trap light structure.
It achieves efficient light absorption and mechanical properties improvement, obtains super-absorbing ability and good mechanical properties, is suitable for large-area rapid preparation, and is suitable for optical systems and new energy fields.
Smart Images

Figure CN118813078B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings, and in particular relates to an ultra-black composite coating based on carbon nanomaterials and a preparation method thereof. Background Art
[0002] Ultra-black materials (also known as super-light-absorbing materials) are a new type of material that can efficiently absorb incident light. They have extremely high light absorption rates and have broad application prospects in scientific research and engineering applications. For example, ultra-black materials can be used to suppress stray light on various ground and space optical platforms, and to improve the detection accuracy, resolution, and detection capabilities of optical systems for dim targets. With the rapid development of aerospace technology, higher requirements are placed on the performance of optical systems. However, the stray light formed by the incident light irradiating the inner wall of the optical system's light shield hinders the satellite-borne optical payload from obtaining high definition and high resolution to a certain extent. To this end, it is necessary to coat the inner wall of the light shield with super-light-absorbing materials to suppress stray light and improve the performance of the optical system. In addition, in the fields of solar energy utilization such as solar evaporation desalination, water evaporation power generation, light-assisted catalytic water treatment, and photothermal conversion, ultra-black materials are also needed to improve the light absorption level. For example, for solar water evaporators, increasing the absorbance helps to improve the water evaporation efficiency at the interface and obtain high solar thermal conversion efficiency.
[0003] The absorption rate of traditional black materials is difficult to exceed 95%, which is difficult to meet the needs of high-sensitivity optical equipment. Researchers have adopted various methods to prepare a variety of ultra-black materials, such as chemical vapor deposition, electrostatic flocking, etching, liquid phase method, etc. These methods construct different micro-nano light trapping structures to obtain super light absorption properties. However. The chemical vapor deposition method requires a fixed-size heating furnace, the sample area prepared is relatively small, and it requires high reaction temperature and high-temperature resistant substrate temperature, high energy consumption, and the carbon nanotube array deposited on the substrate surface has poor impact resistance and is difficult to transfer; the ultra-black material prepared by the electrostatic flocking method is mainly nylon short flocking, which has problems such as large thickness, poor resistance to ultraviolet radiation, and variable angle astigmatism; the etching method has problems such as limited substrate and difficulty in large-area preparation. The liquid phase method has the advantages of simple and flexible process characteristics, meets the needs of roll-to-roll rapid preparation, has the advantages of simple process and low cost, and has better practical application prospects. However, the surface microstructure of the black coating prepared by the existing liquid phase method is often a disordered, uncontrollable porous structure or an uneven extinction structure, and its light absorption capacity still mainly depends on the pigment itself, which is not conducive to obtaining a wide-band super-absorption capacity. In addition, some of the above-mentioned solutions are limited to the pursuit of high absorption rate, and lack the necessary polymer binder, resulting in poor mechanical properties of the coating, which is difficult to meet the needs of practical applications; another part of the large-area coating with a certain adhesion, but the absorption rate in the visible-near infrared band still needs to be further improved, and the problem of difficulty in balancing the mechanical properties and light absorption properties of the coating is still a problem that needs to be solved urgently. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides an ultra-black composite coating based on carbon nanomaterials and a preparation method thereof, which combines ink direct writing 3D printing technology or spraying technology with in-situ ice crystal induced self-assembly technology to construct a flexible, large-area ultra-black composite coating with a vertically ordered micro-nano honeycomb light-trapping structure based on carbon nanomaterials.
[0005] The first object of the present invention is to provide a method for preparing an ultra-black composite coating based on carbon nanomaterials, comprising the following steps:
[0006] S1, dissolving carbon nanoparticle paste, multi-walled carbon nanotube paste, and graphene paste in water and stirring evenly, and continuing to add a binder, a metal oxide filler, a thickener, a defoamer, and an additive and stirring evenly to obtain a composite ink; the carbon nanoparticle paste is obtained by mixing carbon nanoparticles, a first surface modifier, water, and a first alcohol solvent; the multi-walled carbon nanotube paste is obtained by mixing multi-walled carbon nanotubes, a second surface modifier, water, and a second alcohol solvent; the graphene paste is obtained by mixing graphene, a third surface modifier, and water;
[0007] S2, using a spraying technique or an ink direct writing 3D printing technique to form a composite coating on the surface of the substrate using the composite ink described in S1;
[0008] S3. The composite coating described in S2 is subjected to liquid nitrogen freezing treatment by a self-adsorption flat plate freezer, and then freeze-dried by a freeze dryer, and the ultra-black composite coating based on carbon nanomaterials is obtained by plasma surface treatment.
[0009] In one embodiment of the present invention, in S1, the mass parts of the components in the composite ink are: 10-30 parts of carbon nanoparticle paste, 30-50 parts of multi-walled carbon nanotube paste, 10-30 parts of graphene paste, 5-15 parts of water, 1-5 parts of binder, 1-5 parts of metal oxide filler, 0.5-1 parts of thickener, 0.5-1 parts of defoamer, and 1-5 parts of additives;
[0010] The mass ratio of carbon nanoparticles, the first surface modifier, water and the first alcohol solvent in the carbon nanoparticle color paste is (5-15): (5-10): (60-80): (9-20);
[0011] The mass ratio of the multi-walled carbon nanotubes, the second surface modifier, water and the second alcohol solvent in the multi-walled carbon nanotube color paste is (5-10): (5-10): (70-90): (5-12);
[0012] The mass ratio of graphene, the third surface modifier and water in the graphene color paste is (5-20): (5-18): (60-90).
[0013] In one embodiment of the present invention, in S1, the first surface modifier, the second surface modifier and the third surface modifier are independently selected from one or more of disodium distyryl diphenyl disulfonate (DBD), polyvinyl pyrrolidone (PVP) and sodium dodecylbenzene sulfonate (SDBS);
[0014] The first alcohol solvent and the second alcohol solvent are independently selected from one or more of ethanol, isopropanol and ethylene glycol.
[0015] In one embodiment of the present invention, in S1, the binder is selected from one or more of acrylic resin, silicone-modified acrylic resin and epoxy resin;
[0016] The metal oxide filler is selected from nano zinc oxide and / or nano titanium dioxide;
[0017] The thickener is selected from hydroxyethyl cellulose and / or associative polyurethane thickener;
[0018] The defoamer is selected from polysiloxane defoamer and / or BASF Matol defoamer;
[0019] The auxiliary agent is selected from isopropanol and / or ethylene glycol.
[0020] In one embodiment of the present invention, in S2, the substrate is selected from one or more of polyimide film, aluminum alloy, ceramic and wood.
[0021] In one embodiment of the present invention, in S2, the process parameters of the spraying technology are: air pressure of 0.3MPa-0.5MPa, composite ink flow rate of 20mL / min-30mL / min, and spraying distance of 200mm-400mm;
[0022] The process parameters of the ink direct writing 3D printing technology are: air pressure of 100MPa-200MPa, and nozzle movement speed of 20mm / s-30mm / s.
[0023] In one embodiment of the present invention, in S3, the self-adsorption plate freezer is used to achieve rapid freezing of the composite coating on a two-dimensional plane, and the self-adsorption plate freezer includes:
[0024] The first cavity has a micropore array on its surface; the first cavity is connected to an exhaust pipe; the exhaust pipe is connected to a vacuum pump;
[0025] The second cavity is located below the first cavity; the second cavity is provided with an infusion port and an exhaust port; the infusion port is used for infusing liquid nitrogen; the exhaust port is used for exhausting the air in the second cavity.
[0026] In one embodiment of the present invention, in S3, the temperature of the liquid nitrogen freezing is -80°C to -150°C, and the time is 1 min to 5 min;
[0027] In one embodiment of the present invention, in S3, the vacuum degree of freeze drying is 1Pa-10Pa, the temperature is -20℃ to -40℃, and the time is 5h-10h. The in-situ ice crystal induced self-assembly of the composite coating is achieved by freeze casting (liquid nitrogen freezing and freeze drying), the water in the composite coating crystallizes to form hexagonal grains, and the two-dimensional graphene nanosheets with a large width-to-thickness ratio self-assemble into the main skeleton of the vertically and orderly arranged micro-nano honeycomb light-trapping structure under the extrusion of ice crystals; the one-dimensional carbon nanotubes as a reinforcing phase improve the bonding force between the graphene nanosheets, and improve the energy dissipation of the two-dimensional graphene nanosheets when relative slip occurs under the action of external forces, thereby improving the structural strength of the vertically arranged honeycomb structure, so that the composite coating film has better mechanical properties as a whole; zero-dimensional carbon nanoparticles are attached to the surface of graphene and carbon nanotubes to form a nanoscale light-absorbing structure. This vertical and orderly arranged carbon-based micro-nano honeycomb light-trapping structure has micrometer-scale vertical honeycomb holes and nanometer-scale carbon nanopores that can perform multi-level scattering and multiple absorption of incident light to obtain super light absorption ability. This ultra-black composite coating with controllable micro-nano structure, good mechanical properties, and excellent super light absorption performance has great application prospects in the fields of solar thermal conversion water treatment, solar light-assisted catalysis, and stray light suppression of various optical systems in the field of new energy. In particular, the vertically arranged honeycomb structure provides rich sites for further loading other functional nanomaterials to obtain the performance required for other applications, making the ultra-black composite coating have excellent functional scalability.
[0028] In one embodiment of the present invention, in S3, the vacuum degree of the plasma surface treatment is 20Pa-40Pa, the power is 80W-150W, and the time is 1min-5min.
[0029] The second object of the present invention is to provide an ultra-black composite coating based on carbon nanomaterials prepared by the method described.
[0030] The technical solution of the present invention has the following advantages compared with the prior art:
[0031] The preparation method of the present invention uses a composite ink including carbon nanoparticles, multi-walled carbon nanotubes and graphene, and combines the in-situ ice crystal induced self-assembly technology to successfully construct a multi-level micro-nano honeycomb light trapping structure, specifically including a honeycomb skeleton constructed by two-dimensional graphene nanosheets; a nanosheet reinforced skeleton connected by one-dimensional carbon nanotubes, and a nanoscale network is formed on the honeycomb wall; and zero-dimensional carbon nanoparticles are distributed on the network. Such a structure causes the incident light to be lost on multiple scales. The vertical honeycomb on the micrometer scale causes the light to be reflected multiple times. At the reflection point, that is, on the honeycomb wall, the light further enters the carbon nanotube network and is partially absorbed on the one hand, and is scattered and absorbed by the nanoparticles on the carbon tube on the other hand, thereby obtaining super light absorption ability, and the average integral sphere diffuse reflectance in the visible / near infrared band is as low as 0.6%. In addition, since the weakly bound π electrons in the carbon nanotube energy level are easily transitioned to the π antibonding molecular orbital after being excited by the incident light, when the excited electrons return to their ground state through relaxation, heat will be released, so that it has good broadband light absorption ability and light-to-heat conversion ability.
[0032] The preparation method described in the present invention combines ink direct writing 3D printing technology or spraying technology with in-situ ice crystal induced self-assembly technology. Macroscopically, ink direct writing 3D printing technology or spraying technology can achieve precise control of ultra-black composite coatings; microscopically, in-situ ice crystal induced self-assembly technology enables carbon nanoparticles, multi-walled carbon nanotubes and graphene to form a vertically and orderly arranged micro-nano honeycomb light-trapping structure under the extrusion of ice crystals. The preparation method has the advantages of simple and flexible process, low cost, and suitable for rapid preparation of large-area ultra-black composite coatings.
[0033] The vertically and orderly arranged carbon-based micro-nano honeycomb light-trapping structure prepared by the preparation method described in the present invention is a mechanical topological structure, which itself has excellent structural strength. The one-dimensional carbon nanotubes as a reinforcing phase improve the bonding force between graphene nanosheets, and improve the energy dissipation of two-dimensional graphene nanosheets when relative slip occurs under the action of external forces, thereby improving the structural strength of the vertically arranged honeycomb structure, so that the composite coating film has mechanical properties as a whole. In addition, the adhesive used makes the prepared ultra-black coating have good adhesion, improves the mechanical properties of the ultra-black coating, and can maintain the light absorption performance basically unchanged after multiple bending. It solves the problem of mechanical properties of traditional ultra-black materials and meets the needs of practical use. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:
[0035] Figure 1 is a schematic diagram of a self-adsorption plate freezer of the present invention;
[0036] Figure 2 This is a physical picture of the ultra-black composite coating based on carbon nanomaterials according to Example 1 of the present invention;
[0037] Figure 3 The macroscopic optical photographs of the coating of Test Example 1 of the present invention; wherein (a) is the coating of Example 1, (b) is the coating of Example 2, (c) is the coating of Comparative Example 1, and (d) is the coating of Comparative Example 2;
[0038] Figure 4 The SEM images of the coating of Test Example 2 of the present invention; wherein (a) is the coating of Example 1, (b) is the coating of Example 2, (c) is the coating of Comparative Example 1, and (d) is the coating of Comparative Example 2;
[0039] Figure 5 is the integrating sphere diffuse reflectance of the coatings of Examples 1-2 and Comparative Examples 1-2 in Test Example 3 of the present invention;
[0040] Figure 6 is the integrating sphere diffuse reflectance of the coatings of Example 1 and Comparative Example 3 in Test Example 3 of the present invention;
[0041] Figure 7 is the integrating sphere diffuse reflectance of the coatings of Example 1 and Comparative Example 4 in Test Example 3 of the present invention;
[0042] Figure 8 is the integrating sphere diffuse reflectance of the coatings of Example 1 and Comparative Example 5 in Test Example 3 of the present invention;
[0043] Fig. 9 is the integrating sphere diffuse reflectance of the coating of Example 1 before and after bending in Test Example 4 of the present invention;
[0044] Fig.10 is the integrating sphere diffuse reflectance of the coating of Comparative Example 6 in Test Example 4 of the present invention before and after bending;
[0045] Explanation of the reference numerals: 1-first cavity, 1.1-micropore array, 2-exhaust tube, 3-second cavity, 4-injection port, 5-exhaust port. DETAILED DESCRIPTION
[0046] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0047] In the present invention, unless otherwise stated, the experimental methods used in the embodiments of the present invention are conventional methods unless otherwise stated, and the materials, reagents, etc. used are all commercially available unless otherwise stated.
[0048] In the present invention, unless otherwise specified, the carbon nanoparticles used in the embodiments of the present invention are purchased from Mitsubishi Carbon Black, model #1000, and the particle size is about 10nm-20nm; multi-walled carbon nanotubes are purchased from Qihang Technology, with a length of about 10μm-100μm and a diameter of about 10nm-20nm; graphene is purchased from Suzhou Carbon Graphene Technology Co., Ltd., few-layer graphene, with a thickness of about 0.5nm-0.9nm and a sheet diameter of about 5μm-50μm; the binder acrylic resin is purchased from Shanghai Tu Yue New Materials Technology Co., Ltd., model PQ673; the associative polyurethane thickener is purchased from Guangzhou Hui Tu New Materials Co., Ltd., model HT-105; the polysiloxane defoamer is purchased from Guangzhou Tuo Sheng New Materials Co., Ltd., model BYK-025.
[0049] In the present invention, unless otherwise specified, the self-adsorption plate freezer ( Figure 1 ) comprises: a first cavity 1, on the surface of which a micropore array 1.1 is provided; and the side wall of the first cavity 1 is connected to an exhaust pipe 2; the exhaust pipe 2 can be connected to a vacuum pump; a second cavity 3, located below the first cavity 1, is used to charge and discharge low-temperature liquid nitrogen, so that the self-adsorption freezing processor can obtain a low temperature, and the low temperature created by the liquid nitrogen is used to quickly freeze the wet composite coating; the front side wall of the second cavity 3 is provided with an infusion port 4 (funnel shape) for infusing liquid nitrogen; the front side wall of the second cavity 3 is provided with an exhaust port 5 for exhausting the air in the second cavity 3. Example 1
[0050] The ultra-black composite coating based on carbon nanomaterials and the preparation method thereof of the present invention specifically include the following steps:
[0051] S1: Preparation of carbon nanomaterial color paste
[0052] S11, preparation process of carbon nanoparticle color paste: weigh 10 parts of carbon nanoparticles, 5 parts of surface modifier polyvinyl pyrrolidone, 75 parts of water, and 10 parts of alcohol solvent ethylene glycol, add them into a dispersion tank, first use a mechanical shear disperser to stir and disperse for 30 minutes at a stirring speed of 2000rpm, then use a power of 500W to ultrasonically disperse, and then use a three-roller mill with a roller spacing of 5μm to grind 5 times to obtain a carbon nanoparticle color paste;
[0053] S12. Preparation of multi-walled carbon nanotube color paste: weigh 5 parts of multi-walled carbon nanotubes, 5 parts of surface modifier sodium dodecylbenzene sulfonate, 80 parts of water, and 10 parts of alcohol solvent isopropanol, add them into a dispersion tank, first use a mechanical shearing disperser to stir and disperse at a stirring speed of 1000 rpm for 30 minutes, then use a power of 500 W to ultrasonically disperse for 30 minutes, and then use a high-pressure homogenizer to disperse 5 times at a pressure of 800 bar to obtain a multi-walled carbon nanotube color paste;
[0054] S13. Preparation of graphene color paste: Weigh 5 parts of graphene, 5 parts of surface modifier polyvinyl pyrrolidone, and 90 parts of water, add them into a dispersion tank, first use a mechanical shear disperser to stir and disperse them at a stirring speed of 3000 rpm for 30 minutes, and then ultrasonically disperse them at a power of 800 W for 30 minutes to obtain graphene color paste.
[0055] S2: Preparation of composite ink
[0056] Take 20 parts of carbon nanoparticle color paste, 40 parts of multi-walled carbon nanotube color paste, and 20 parts of graphene color paste and add them to a dispersion tank filled with 12 parts of deionized water, and stir and mix them for 60 minutes using a mechanical shear disperser at a stirring speed of 2000 rpm; continue to slowly add 5 parts of a binder acrylic resin emulsion with a solid content of 40%, 1 part of a metal oxide filler nano titanium dioxide, 0.5 parts of an associative polyurethane thickener, 0.5 parts of a polysiloxane defoamer and 1 part of an auxiliary isopropanol under stirring conditions, and continue to stir and mix for 60 minutes to obtain a composite ink.
[0057] S3: Preparation of composite coating
[0058] S31, treating the surface of the flexible polyimide film substrate with a low-temperature surface plasma having a power of 1 kW for 20 seconds, and then pickling with 10% by volume sulfuric acid for 1 hour to complete the hydrophilic treatment of the surface of the flexible polyimide film substrate to obtain a pretreated substrate;
[0059] S32. Using the ink direct writing 3D printing technology, the air pressure is set to 100 MPa, the nozzle movement speed is set to 20 mm / s, and the composite ink is placed on the surface of the pretreated substrate to obtain a composite coating.
[0060] S4: Preparation of ultra-black composite coatings based on carbon nanomaterials
[0061] S41, spreading the composite coating on the surface of a self-adsorption plate freezer filled with liquid nitrogen and freezing it at -120°C for 1 minute;
[0062] S42, freeze drying for 8 hours in a freeze dryer at a vacuum degree of 4 Pa and a temperature of -40°C, forming a vertically and orderly arranged micro-nano honeycomb light trapping structure through liquid nitrogen freezing and freeze drying;
[0063] S43, finally, oxygen plasma surface treatment was performed for 5 min under the conditions of 40 Pa vacuum and 120 W power in the chamber to etch the honeycomb wall at the top of the vertically and orderly arranged micro-nano honeycomb light trapping structure to obtain an ultra-black composite coating based on carbon nanomaterials ( Figure 2 ). Example 2
[0064] The method is basically the same as Example 1, except that the ink direct writing 3D printing technology is replaced by the spraying technology, and specifically includes the following steps:
[0065] By using the spraying technology, the air pressure was set to 0.3 MPa, the composite ink flow rate was set to 30 mL / min, the spraying distance was set to 250 mm, and the composite ink was placed on the surface of the pretreated substrate to obtain a composite coating. Comparative Example 1
[0066] The method is basically the same as Example 1, except that the prepared composite coating is not subjected to subsequent in-situ ice crystal induced self-assembly treatment. Comparative Example 2
[0067] The method is basically the same as Example 2, except that the prepared composite coating is not subjected to subsequent in-situ ice crystal induced self-assembly treatment. Comparative Example 3
[0068] The method is basically the same as Example 1, except that no carbon nanoparticle color paste is added to the composite ink. Comparative Example 4
[0069] The method is basically the same as Example 1, except that no multi-walled carbon nanotube color paste is added to the composite ink. Comparative Example 5
[0070] The method is basically the same as Example 1, except that no graphene color paste is added to the composite ink. Comparative Example 6
[0071] The method is basically the same as Example 1, except that no binder is added to the composite ink.
[0072] Test Example 1
[0073] The macroscopic optical photographs of the coatings prepared in Examples 1-2 and Comparative Examples 1-2 are as follows: Figure 3 As shown. Figure 3 (a)- Figure 3 (b) It can be seen that the coating of Example 1-2 is dark black, uniform in color, and has no visible reflection. Figure 3 (c)- Figure 3 (d) It can be seen that the coating of Comparative Example 1-2 is gray and uniform in color.
[0074] Test Example 2
[0075] The SEM images of the coatings prepared in Examples 1-2 and Comparative Examples 1-2 are as follows: Figure 4 As shown. Figure 4 (a)- Figure 4 (b) It can be seen that the coating of Example 1-2 presents a micro-nano honeycomb light trapping structure, and the diameter of the honeycomb holes is about 10μm-50μm. Figure 4 (c)- Figure 4(d) It can be seen that the coating surface of Comparative Example 1-2 is smooth and dense.
[0076] Test Example 3
[0077] The integrating sphere diffuse reflectance curves of the coatings prepared in Examples 1-2 and Comparative Examples 1-6 were tested using a LAMBDA 1050+ UV-visible-near-infrared spectrophotometer with an integrating sphere accessory. The wavelength range was 400nm-2000nm. The results are as follows: Figure 5-Figure 8 shown.
[0078] from Figure 5 It can be seen that the coating of Example 1-2 has an average reflectivity of about 0.6% (absorption of about 99.4%) in the visible and near-infrared (Vis / NIR) bands. The coating of Comparative Example 1-2 has an average reflectivity of about 1.7% (absorption of about 98.3%) in the visible and near-infrared (Vis / NIR) bands. This is because the examples combine spraying / 3D printing and ice crystal induced self-assembly technology in the preparation process. The prepared coating is microscopically composed of two-dimensional graphene nanosheets that self-assemble under the extrusion of ice crystals into the main skeleton of a vertically and orderly arranged micro-nano honeycomb light-trapping structure; one-dimensional carbon nanotubes act as a reinforcing phase to increase the bonding force between graphene nanosheets, while forming a continuous porous network on the honeycomb wall; zero-dimensional carbon nanoparticles are attached to the surface of graphene and carbon nanotubes. This multi-level and multi-scale light-trapping structure ( Figure 4 (a)- Figure 4 (b)); while the coating obtained in the comparative example without the ice crystal induced self-assembly technique showed an almost planar structure at the microscopic level ( Figure 4 (c)- Figure 4 (d)). This makes the light reflectivity of the coating of the embodiment much lower than that of the comparative example ( Figure 5 ), which is reflected in the macroscopic view that the coating color of the embodiment is uniformly black, while the coating of the comparative example is gray, which is a significant difference ( Figure 3 ).
[0079] from Figure 6 It can be seen that since zero-dimensional carbon nanoparticles are not added to the ink in Comparative Example 3, the coating prepared lacks some light scattering sites compared to the coating prepared in Example 1, and the light trapping effect is poor, which makes the reflectivity of the coating prepared in Comparative Example 3 higher than that in Example 1.
[0080] from Figure 7 It can be seen that since the comparative example 4 does not add one-dimensional carbon nanotubes to the ink, the coating prepared cannot form an interwoven carbon nanotube network with nanopores compared to the coating prepared in Example 1, and the light trapping effect is poor, which makes the reflectivity of the coating prepared in Comparative Example 4 higher than that in Example 1.
[0081] from Figure 8It can be seen that since the two-dimensional graphene is not added to the ink in Comparative Example 5, the honeycomb structure walls formed by the prepared coating are thicker than those of the coating prepared in Example 1, part of the light cannot enter the inside of the holes, and the light trapping effect is poor, which makes the reflectivity of the coating prepared in Comparative Example 5 higher than that in Example 1.
[0082] Test Example 4
[0083] The coatings prepared in Example 1 and Comparative Example 6 were bent 90° 10 times, and the integrating sphere diffuse reflectance curves before and after the bending were as follows: Figure 9-10 As shown. Fig. 9 It can be seen that after the coating of Example 1 was bent 90° repeatedly 10 times, its reflectivity was almost unchanged compared with that before the bending, which indicates that the ultra-black film prepared in Example 1 maintained its light absorption performance basically unchanged after being bent multiple times. Fig.10 It can be seen that after the coating of Comparative Example 6 was repeatedly bent at 90° for 10 times, the coating fell off severely due to the lack of adhesive, resulting in a significant increase in reflectivity after bending. This indicates that compared with the embodiment, the coating obtained in Comparative Example 6 has poor durability.
[0084] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A method for preparing an ultra-black composite coating based on carbon nanomaterials, characterized in that: The following steps are involved: S1, dissolving carbon nanoparticle paste, multi-walled carbon nanotube paste, and graphene paste in water and stirring evenly, and continuing to add a binder, a metal oxide filler, a thickener, a defoamer, and an additive and stirring evenly to obtain a composite ink; the carbon nanoparticle paste is obtained by mixing carbon nanoparticles, a first surface modifier, water, and a first alcohol solvent; the multi-walled carbon nanotube paste is obtained by mixing multi-walled carbon nanotubes, a second surface modifier, water, and a second alcohol solvent; the graphene paste is obtained by mixing graphene, a third surface modifier, and water; the binder is an acrylic resin; the first surface modifier, the second surface modifier, and the third surface modifier are independently selected from polyvinyl pyrrolidone and / or sodium dodecylbenzene sulfonate; The weight parts of the components in the composite ink are: 10-30 parts of carbon nanoparticle paste, 30-50 parts of multi-walled carbon nanotube paste, 10-30 parts of graphene paste, 5-15 parts of water, 1-5 parts of binder, 1-5 parts of metal oxide filler, 0.5-1 parts of thickener, 0.5-1 parts of defoamer, and 1-5 parts of additive; The mass ratio of carbon nanoparticles, the first surface modifier, water and the first alcohol solvent in the carbon nanoparticle color paste is (5-15): (5-10): (60-80): (9-20); The mass ratio of the multi-walled carbon nanotubes, the second surface modifier, water and the second alcohol solvent in the multi-walled carbon nanotube color paste is (5-10): (5-10): (70-90): (5-12); The mass ratio of graphene, the third surface modifier and water in the graphene color paste is (5-20): (5-18): (60-90); S2, using a spraying technique or an ink direct writing 3D printing technique to form a composite coating on the surface of the substrate using the composite ink described in S1; S3. The composite coating described in S2 is subjected to liquid nitrogen freezing treatment by a self-adsorption flat-plate freezer, and then freeze-dried by a freeze dryer, to form a vertically and orderly arranged micro-nano honeycomb light-trapping structure by liquid nitrogen freezing and freeze-drying, and finally plasma surface treatment is performed to etch the honeycomb wall at the top of the vertically and orderly arranged micro-nano honeycomb light-trapping structure to obtain the ultra-black composite coating based on carbon nanomaterials.
2. The method for preparing the ultra-black composite coating based on carbon nanomaterials according to claim 1, characterized in that: In S1, the first alcohol solvent and the second alcohol solvent are independently selected from one or more of ethanol, isopropanol and ethylene glycol.
3. The method for preparing the ultra-black composite coating based on carbon nanomaterials according to claim 1, characterized in that: In S1, the metal oxide filler is selected from nano zinc oxide and / or nano titanium dioxide; The thickener is selected from hydroxyethyl cellulose and / or associative polyurethane thickener; The defoamer is a polysiloxane defoamer; The auxiliary agent is selected from isopropanol and / or ethylene glycol.
4. The method for preparing the ultra-black composite coating based on carbon nanomaterials according to claim 1, characterized in that: In S2, the process parameters of the spraying technology are: air pressure of 0.3MPa-0.5MPa, composite ink flow rate of 20mL / min-30mL / min, and spraying distance of 200mm-400mm; The process parameters of the ink direct writing 3D printing technology are: air pressure of 100MPa-200MPa, and nozzle movement speed of 20mm / s-30mm / s.
5. The method for preparing the ultra-black composite coating based on carbon nanomaterials according to claim 1, characterized in that: In S3, the self-adsorption plate freezer comprises: The first cavity has a micropore array on its surface; the first cavity is connected to an exhaust pipe; the exhaust pipe is connected to a vacuum pump; The second cavity is located below the first cavity; the second cavity is provided with an infusion port and an exhaust port; the infusion port is used for infusing liquid nitrogen; the exhaust port is used for exhausting the air in the second cavity.
6. The method for preparing the ultra-black composite coating based on carbon nanomaterials according to claim 1, characterized in that: In S3, the temperature of the liquid nitrogen freezing is -80°C to -150°C, and the time is 1 min to 5 min.
7. The method for preparing an ultra-black composite coating based on carbon nanomaterials according to claim 1, characterized in that: In S3, the vacuum degree of freeze drying is 1Pa-10Pa, the temperature is -20°C to -40°C, and the time is 5h-10h.
8. The method for preparing an ultra-black composite coating based on carbon nanomaterials according to claim 1, characterized in that: In S3, the vacuum degree of the plasma surface treatment is 20Pa-40Pa, the power is 80W-150W, and the time is 1min-5min.
9. An ultra-black composite coating based on carbon nanomaterials prepared by the method according to any one of claims 1 to 8.
